VARIATIONS IN LENGTH OF STYLOID PROCESS IN ADULT HUMAN DRY SKULLS - Muneera, Mahjabeen; Hina, Mohtasham; Bukhari, Zahra Haider; Kuraishi, Raafea Tafweez (Pakistan Armed Forces Medical Journal, 2021)
Objective: To establish baseline data regarding average length of styloid process in adult human dry skulls in Asian population in Pakistani region. Study Design: Comparative cross sectional study. Place and Duration of Study: Department of Anatomy King Edward Medical University, University of Lahore, Services Institute of Medical Sciences, Central Park Medical College, CMH Lahore and Nawaz Sharif Medical College Gujrat, from May to Jun 2018. Methodology: A total of 71 adult human dry skulls with intact styloid processes were studied from the Anatomy museums of various public and private sector medical colleges of Punjab. The length of both styloid processes from root to tip was measured using a measuring scale in centimetres. Results: The length of styloid process varied from a minimum value of 0.8 cm to a maximum value of 4.3cm. Mean length of right and left styloid processes was found to be 1.68 ±.781cm and 1.86 ±.738cm respectively. Out of 14.2% of skulls were found to have styloid process >2.5cm. Mean length of styloid process of the skulls studied in our setting is 1.77 ± 0.76cm. Conclusion: As the styloid process was found to be longer than the normal reported length in 14% of skulls. It might be a reason for symptomatic patients presenting in outpatient ward with throat pain and discomfort which often remains unaddressed and needs consideration.